The Protective Effect of Aromatase on NSC-34 Cells with Stably Expressed hSOD1-G93A. (15th July 2019) - Yan, Lina; Qi, Weijing; Liu, Yaling; Zhou, Fuling; Wang, Yafei; Bai, Lin; Zhou, Xiaomeng; Sun, Can; Nie, Xiangyu; Duan, Shiru; Ran, Jina; Chen, Juan; et al.
Abstract: As an adult-onset neurodegenerative disease, amyotrophic lateral sclerosis (ALS) results in progressive muscular atrophy and paralysis. However, the mechanism of ALS has not yet been elucidated, and no cure has been found. Research has revealed that a mutation of the Cu/Zn superoxide dismutase (SOD1) gene is linked to familial ALS and that potential sex discrepancies exist in ALS incidence. Here, NSC-34 cells stably expressing hSOD1-G93A (hSOD1-G93A cells) were transiently transfected with Cyp19a1 mouse open reading frame (ORF) cDNA or a short hairpin RNA (ShRNA) plasmid. Overexpression of aromatase resulting from Cyp19a1 mouse ORF cDNA plasmid transfection enhanced cell proliferation and reduced cell damage in hSOD1-G93A cells. This protective effect occurred through anti-apoptotic pathways related to estrogen receptor-alpha (ER-α) activation. Meanwhile, knockdown of aromatase with Cyp19a1 ShRNA plasmid transfection reduced cell proliferation, increased cell damage, promoted apoptosis, and decreased ER-α expression in hSOD1-G93A cells, and the induced apoptotic effects could be reversed by estradiol (E2). In brief, the results of our study suggest that aromatase plays a neuroprotective role against apoptosis in hSOD1-G93A cells by activating ER-α and may become a new intervention target for ALS treatment. Highlights: Aromatase played a neuroprotective role through an anti-apoptosis mechanism in hSOD1-G93A cells. E2 reversed the apoptotic effect of aromatase knockdown. The anti-apoptotic effect of aromatase was related to ER-α activation.